2001
DOI: 10.1046/j.1365-2672.2001.01463.x
|View full text |Cite
|
Sign up to set email alerts
|

The Gram-positive tonsillar and nasal flora of piglets before and after weaning

Abstract: Aims: To investigate Gram‐positive nasal and tonsillar microbial flora of piglets before and after weaning. Methods and Results: The nasal and tonsillar Gram‐positive bacterial flora of 20 non‐weaned piglets (2 weeks of age) and 20 weaned piglets (6 weeks of age), obtained from four different piggeries, was quantified by culture and identified by tDNA‐PCR. The most widely occurring species from nasal conchae before as well as after weaning in the different piglets investigated were Streptococcus suis and Roth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 24 publications
5
48
0
2
Order By: Relevance
“…One 2013 experimental study reported markedly higher numbers of S. aureus in pharyngeal (including tonsil) tissues of pigs than in nasal samples, 12 and a similar observation was reported for naturally infected pigs. 2 The importance of the oropharynx as a site of colonization of people with S. aureus is well established, with several studies reporting higher prevalence in oropharyngeal than nasal samples. 29 It has been suggested that housing of pigs in isolation could give some insight into which locations are most supportive of S. aureus persistence.…”
Section: Discussionmentioning
confidence: 99%
“…One 2013 experimental study reported markedly higher numbers of S. aureus in pharyngeal (including tonsil) tissues of pigs than in nasal samples, 12 and a similar observation was reported for naturally infected pigs. 2 The importance of the oropharynx as a site of colonization of people with S. aureus is well established, with several studies reporting higher prevalence in oropharyngeal than nasal samples. 29 It has been suggested that housing of pigs in isolation could give some insight into which locations are most supportive of S. aureus persistence.…”
Section: Discussionmentioning
confidence: 99%
“…T he respiratory, alimentary, and genital tracts of healthy pigs are commonly colonized by Streptococcus suis (1,2). However, S. suis is also one of the most important porcine pathogens, causing different pathologies such as meningitis, septicemia, arthritis, and endocarditis (3).…”
mentioning
confidence: 99%
“…During an investigation of the tonsillar and nasal flora of piglets with tRNA-intergenic spacer length polymorphism analysis (tDNA-PCR) (Baele et al, 2001a), a group of Gram-positive coccal isolates was isolated and characterized further. Representative strains were studied extensively and were found to belong to the poorly described species Streptococcus ferus.…”
mentioning
confidence: 99%